The Oppressive Pressures of Globalization and Neoliberalism on Mexican Maquiladora Garment Workers - Jenna Demeter (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2019)
The international economic trends of globalization and neoliberalism have exposed and enabled the exploitation of Mexican workers, especially women in the maquiladora garment industry. During the 1950s, globalization gave rise to the new international division of labor and transnational corporations (TNCs) that have offshored labor-intensive phases of production to developing countries, many of which have pursued export-led industrialization. Export processing in Mexico was encouraged in the 1960s by Item 807 of the U.S. Tariff Code and Mexico’s Border Industrialization Program. Especially following the Latin American debt crisis of the 1980s, advanced capitalist countries and International Financial Institutions foisted neoliberal structural adjustment on Latin American countries, including further trade liberalization and the reduction of social and public expenditure. Despite its detriment to the laboring majority, Mexican and U.S. elite have selfishly perpetuated neoliberal policy through Mexican governance by repressive proponents and the North Atlantic Free Trade Agreement (NAFTA). Mexico’s consequential economic dependence on advanced countries has weakened the position of labor and contributed to economic crises that have devastated the national productive structure and turned desperate citizens toward precarious work in exporting industries. Flexible accumulation, especially in the highly-mobile garment industry, has allowed TNCs to have complex international networks without commitment, causing oppressive competition between global workers. While Mexico has competed for export processing by offering an efficient, low-cost, and disciplined workforce, restructuring has also limited labor protection and social services at the expense of the working class.
Keywords: Export-led industrialization; transnational corporations (TNCs); offshoring; structural adjustment; exploitation; garment industry; sweatshop